The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s00040-008-1025-2
|View full text |Cite
|
Sign up to set email alerts
|

Venom alkaloids of monogyne and polygyne forms of the red imported fire ant, Solenopsis invicta, in Taiwan

Abstract: Both monogyne and polygyne colonies of Solenopsis invicta now occupy Taiwan. Although venom alkaloids of these ants have been described and synthesized, we here report on a quantitative analysis of the two social forms for the first time. The alkaloids were studied by gas chromatography coupled to mass spectrometry (GC-MS), and six major venom alkaloids were detectable in both types of workers. Both C 13 :C 13:1 and C 15 :C 15:1 ratios in alkaloid venom of monogyne workers were statistically higher than that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…A Finnigan Focus GC was coupled to a Finnigan Focus DSQ mass selective detector (Thermo Fisher, Waltham, MA) to separate and identify the venom alkaloids of S. geminata according to our previous publication (Lai et al 2008). The mass spectral base peak at m/z ϭ 98 corresponded to the fragment C 6 H 12 N ϩ (MacConnell et al 1971).…”
Section: Collection Of Venom and Chemical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…A Finnigan Focus GC was coupled to a Finnigan Focus DSQ mass selective detector (Thermo Fisher, Waltham, MA) to separate and identify the venom alkaloids of S. geminata according to our previous publication (Lai et al 2008). The mass spectral base peak at m/z ϭ 98 corresponded to the fragment C 6 H 12 N ϩ (MacConnell et al 1971).…”
Section: Collection Of Venom and Chemical Analysesmentioning
confidence: 99%
“…Our previous study showed that venom alkaloids of S. invicta vary with the social forms (monogyne versus polygyne workers) and the sampling methods (microcapillary tube versus whole body soaking) (Lai et al 2008). We hypothesized that the venom composition of major workers and minor workers of S. geminata may also differ because of different sampling methods used.…”
mentioning
confidence: 99%
“…Milking venom into a capillary tube placed on the sting was first described by Blum et al (1958), and later widely used in obtaining pure venom for compositional analyses or bioassays (MacConnell et al 1970;1971;Brand et al 1972Brand et al , 1973bMacConnell et al 1976;Blum 1992;Greenberg et al 2008;Lai et al 2008Lai et al , 2009Lai et al , 2012. In this way, milligram quantities of pure venom can be obtained for direct use.…”
Section: Introductionmentioning
confidence: 99%
“…This method can be used to obtain a large amount of venom by successively extracting multiple ants. Although such extracts have been used directly in chemical analysis (Deslippe & Guo 2000;Lai et al 2008Lai et al , 2009Eliyahu et al 2011), further purification steps are needed to obtain pure venom alkaloid fractions. Chen and Fadamiro (2009a) developed a practical method to purify venom alkaloids by washing the whole body extract with a hexane-acetone solvent system containing 1 to 2% triethylamine through a silica gel column (See details in Yu et al 2014;Shi et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Differences between the proportions of unsaturated alkaloids and ratios of C 13 : C 13:1 and C 15 :C 15:1 alkaloids in the venom of the monogyne and polygyne forms of S. invicta have been demonstrated (Lai et al 2008). The effects of environmental cues on the venom compositions of S. invicta and S. geminata in Taiwan were further characterized in our previous studies (Lai et al 2008(Lai et al , 2009).…”
mentioning
confidence: 89%